Isolation and Identification of Cancer Stem-Like Cells in Adenocarcinoma and Squamous Cell Carcinoma of the Lung: A Pilot Study - Masciale, Valentina; Grisendi, Giulia; Banchelli, Federico; D'Amico, Roberto; Maiorana, Antonino; Sighinolfi, Pamela; Stefani, Alessandro; Morandi, Uliano; Dominici, Massimo; Aramini, Beatrice (Frontiers in Oncology, 2019)
Background: Lung cancer stem cells (CSCs) share many characteristics with normal stem cells, such as self-renewal and multipotentiality. High expression of aldehyde dehydrogenase (ALDH) has been detected in many tumors, particularly in the CSC compartment, and it plays an important role in tumor proliferation, metastasis, and drug resistance. CD44 is commonly used as a cell surface marker of cancer stem-like cells in epithelial tumors. The aim of this study was to isolate and analyze cancer stem-like cells from surgically removed specimens to compare lung adenocarcinoma (ADENO) and squamous (SQUAMO) cell carcinoma. Methods: The ALDEFLUOR assay was used to identify and sort ALDHhigh and ALDHlow human lung cancer cells following tissue digestion. Fluorescence-activated cell sorting analysis for CD44 was performed with tumor cells. Quantitative real-time PCR was performed to assess the expression of SOX2 and NANOG as stemness markers. ALDH1A1 expression was additionally determined by immunohistochemistry. Anchorage-independent ALDHhigh cell growth was also evaluated. ALDHhigh ADENO and SQUAMO cells were cultured to analyze spheroid formation. Results: All specimens contained 0.5–12.5% ALDHhigh cells with 3.8–18.9% CD44-positive cells. SOX2 and NANOG relative expression in ALDHhigh compared to ALDHlow cells in ADENO and SQUAMO was analyzed and compared between the histotypes. Immunohistochemistry confirmed the presence of ALDH1A1 in the sections. SOX2 and NANOG were expressed at higher levels in the ALDHhigh subpopulation than in the ALDHlow subpopulation only in ADENO cells, and the opposite result was seen in SQUAMO cells. In vitro functional assays demonstrated that ALDHhigh cells exhibited migration capacity with distinct behaviors between ALDHhigh spheres in ADENO vs. SQUAMO samples. Conclusions: Our results highlight the importance of a better characterization of cancer stem-like cells in ADENO and SQUAMO histotypes. This may suggest new differential approaches for prognostic and therapeutic purposes in patients with non-small-cell lung cancer.